Transcriptomic and open chromatin atlas of high-resolution anatomical regions in the rhesus macaque brain - Yin, Senlin (Nat Commun, 2020)
The rhesus macaque is a prime model animal in neuroscience. A comprehensive transcriptomic and open chromatin atlas of the rhesus macaque brain is key to a deeper understanding of the brain. Here we characterize the transcriptome of 416 brain samples from 52 regions of 8 rhesus macaque brains. We identify gene modules associated with specific brain regions like the cerebral cortex, pituitary, and thalamus. In addition, we discover 9703 novel intergenic transcripts, including 1701 coding transcripts and 2845 lncRNAs. Most of the novel transcripts are only expressed in specific brain regions or cortical regions of specific individuals. We further survey the open chromatin regions in the hippocampal CA1 and several cerebral cortical regions of the rhesus macaque brain using ATAC-seq, revealing CA1- and cortex-specific open chromatin regions. Our results add to the growing body of knowledge regarding the baseline transcriptomic and open chromatin profiles in the brain of the rhesus macaque.